Implementation of Disaster Recovery Planning in Call Center System - Fajar Muttaqi (Scientific Journal of Information System, 2024)
Call center management refers to how leaders manage the center and includes activities such as forecasting, scheduling, queue management, agent training and coaching, and, of course, ensuring customer contacts are handled professionally and efficiently. Call Center services in Indonesia do not reach the public. To achieve this, a call center is used for business services. To reach the target, effective call center performance is needed by the call center system appropriately. DRP is one of the solutions to reduce the data risk, because of disasters and other threats. So the system has another backup.